Answer:
[tex]m = n[/tex] --> Corresponding angle
[tex]x = y[/tex] --> Vertically opposite
Step-by-step explanation:
Given
The attachment
Required
State the reason for the given statements
m = n
m and n are corresponding angles.
So:
[tex]m = n[/tex]
x = y
x and y are vertically opposite angles
So:
[tex]x = y[/tex]
[tex]y + n = x + m[/tex]
In (b)
[tex]x = y[/tex]
Add m to both sides
[tex]x + m = y +m[/tex]
In (a) [tex]m = n[/tex]
So, substitute n for m on the left hand side
[tex]x + n = y + m[/tex]